Using Ultrasonic Waves to Determine the Microstructure of Snow - Lieblappen, Ross; Fegyveresi, John M.; Courville, Zoe; Albert, Donald G. (Frontiers in Earth Science, 2020)
Acoustic signals interact with the physical structure of porous media, are particularly sensitive to porosity and tortuosity, and can be used to measure physical properties in a non-destructive manner. Given the fragile nature of freshly fallen snow, non-contact, non-destructive characterization methods made possible via acoustic signals, are desirable. High frequency wave propagation methods can be used to determine in-situ, near-surface, micro-pore geometry parameters in snow using methods demonstrated on cohesive porous materials, including manufactured foams, porous metals, and sintered glass beads. High frequency (90 kHz), oblique-angle and near vertical reflection measurements were conducted on snow samples in a cold room to demonstrate the feasibility of acoustic characterization. A nonlinear least squares regression to the theoretical reflection response was used to derive the best-fitting values for the porosity and tortuosity. We compared the acoustically-derived snow physical parameters, including porosity and tortuosity, with values determined from X-ray micro-computed tomography (μCT) for different snow types. The μCT-measured and acoustically-derived methods demonstrated strong agreement for porosity with differences averaging 8% for all samples. Tortuosity values, however, had average differences of roughly 20% for all samples. The different error rates might be caused by the stronger dependence of the acoustic reflection on porosity than on tortuosity. For both parameters, the small grain snow and large grain firn samples had errors much larger than the fresh or 1 day samples. Fresh snow has the lowest reflection coefficients and demonstrates a steady decrease from <0.1 at normal incidence as the angle increases. Aging fresh snow for 1 day caused detectable changes in acoustic response, from slight decreases in porosity, and slight increases in tortuosity that occurred from sintering.